2011
DOI: 10.1111/j.1442-200x.2010.03310.x
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T and A1298C polymorphisms as a risk factor for congenital heart defects in Down syndrome

Abstract: Because the fetus is lost in a great proportion of trisomy 21 pregnancies, both maternal and fetal, not only live-born MTHFR C677T and A1298C, as well as maternal nutrition and lifestyle during pregnancy, should be analyzed to asses the impact on CHD in DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…[27] Data on the genotype and allele frequencies of MTHFR C677T polymorphism in DS mothers compared to non-DS mothers are numerous and show significant differences, but reports regarding distribution of MTHFR mutant allele and genotype frequencies in DS individuals are very few. [192930313233] Several clinical and experimental studies have hypothesized/reported that patients with DS have disturbed one-carbon metabolism. [23] t-Hcy, vitamin B-12 and folate are metabonutritional factors directly related to this metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…[27] Data on the genotype and allele frequencies of MTHFR C677T polymorphism in DS mothers compared to non-DS mothers are numerous and show significant differences, but reports regarding distribution of MTHFR mutant allele and genotype frequencies in DS individuals are very few. [192930313233] Several clinical and experimental studies have hypothesized/reported that patients with DS have disturbed one-carbon metabolism. [23] t-Hcy, vitamin B-12 and folate are metabonutritional factors directly related to this metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Also the functional MTHFR c.1298A polymorphism was over-transmitted to cases with atrioventricular septal defects (P = 0.05) and under-transmitted to controls (P = 0.02) 8 . By contrast, others have failed to observe the association of maternal MTHFR polymorphisms with CHDs in the DS offspring 27 . The study population included 112 DS subjects and CHDs were present in 48% of the DS subjects.…”
Section: Maternal Folate Metabolism and Risk Of Congenital Heart Defementioning
confidence: 94%
“…The study population included 112 DS subjects and CHDs were present in 48% of the DS subjects. The mothers of 107 DS individuals were available for the study and none were peri-conceptional folic acid users 27 . However, despite some conflicting results, the vast majority of recent studies suggest that lack of folic acid supplementation at peri-conception coupled with genetic variants of the folate metabolic pathway might represent maternal risk factors for CHDs in the DS child (Table 3).…”
Section: Maternal Folate Metabolism and Risk Of Congenital Heart Defementioning
confidence: 99%
“…Results about DS and MTHFRC677T polymorphism as a risk factor of its occurrence are still conflicting. The recent meta-analysis suggested that MTHFR 677T is a major risk factor for DS birth [105], while previous smaller studies did not recognize such risk [106,107]. Studies performed analyzing peripheral lymphocytes of women with DS offspring revealed several markers of global genome instability, including an increased frequency of micronuclei, shorter telomeres, and impaired DNA methylation at MTHFR promoter [108,109].…”
Section: Epigenetic Genetic and Nutrigenomic Risk Factors For Congementioning
confidence: 99%